Investigating the Chemical Composition of "Rheum tataricum" Growing in the Harsh Climatic Conditions of Uzbekistan (Progress Annals: Journal of Progressive Research, 2026)
The diverse flora of Uzbekistan presents a rich source of information for researchers interested in phytochemistry and adaptation. Among these, the genus Rheum, and particularly Rheum tataricum, attracts attention due to its notable resilience to difficult environmental factors. Distributed across semi-arid and mountainous regions, often where soil salinity, temperature fluctuations, and periodic droughts are prevalent, this species exhibits morphological and physiological mechanisms that speak to its adaptive versatility. As such, a detailed analysis of its chemical composition not only enlightens chemotaxonomic relationships but also elucidates strategies for survival under environmental stress, in addition to providing insight into potential pharmaceutical and nutraceutical uses.